Electrical Machines:for GATE - ESE/ PSU and other competitive exams / Goyal, Ankit (KREATRYX Pub., 2018)
Electrical Machines:for GATE/ESE/ PSU and other competitive exams / Goyal, Ankit. -- New Delhi: KREATRYX Pub., 2018 153.9462131042 G724 No. of Copies : 6